2022
DOI: 10.1159/000527159
|View full text |Cite
|
Sign up to set email alerts
|

Association between 19 Allergens and Chronic Constipation in Adults: NHANES 2005–2006

Abstract: <b><i>Introduction:</i></b> There are increasing reports of a link between chronic constipation and allergies in children. However, similar epidemiological evidence is limited in the general adult population. Therefore, in this study, we attempted to assess the association between chronic constipation and allergy in adults aged ≥20 years in the USA. <b><i>Methods:</i></b> We established a logistic regression model to test the relationship between chronic constipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Three Taiwanese cohort studies reported that constipation was a risk factor for allergic dermatitis [ 10 ], allergic rhinitis [ 11 ], and asthma [ 9 ]. On the other hand, in a US study, food allergies including peanut, eggs, and allergies to dogs and cockroaches are inversely associated with the prevalence of constipation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three Taiwanese cohort studies reported that constipation was a risk factor for allergic dermatitis [ 10 ], allergic rhinitis [ 11 ], and asthma [ 9 ]. On the other hand, in a US study, food allergies including peanut, eggs, and allergies to dogs and cockroaches are inversely associated with the prevalence of constipation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected at the NHANES examination site and analyzed in the NHANES laboratory, and serum total IgE was tested using the Pharmacia Diagnostics ImmunoCAP 1000 System (Kalamazoo, MI, USA) (Min & Min, 2019 ; Xi et al., 2023 ). Total IgE was analyzed as a continuous variable, while participants were categorized into two groups according to total IgE levels: normal total IgE levels (2.5–100 kU/L) and high total IgE levels (100–1000 kU/L), with the latter indicating total IgE sensitization (Ferastraoaru & Rosenstreich, 2018 ; Xi et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering that age, gender, race, BMI, alcohol consumption, smoking, diabetes, hypertension, and physical exercise may affect E‐DII and total IgE, these variables were included in multivariable models (Min & Min, 2019 ; Sun et al., 2023 ; Xi et al., 2023 ). Smoking, alcohol consumption, and physical exercise were determined based on responses to the relevant questions.…”
Section: Methodsmentioning
confidence: 99%